ANALYSIS OF THE CIRCLE OF PEACE FOUNDATION'S AND BNPT'S COLLABORATION IN THE SUCCESSFUL DERADICALIZATION PROGRAM FOR TERRORISM INMATES IN SURABAYA'S CLASS I CORRECTIONAL INSTITUTIONS - Adhyaksa, Deva Kharisma; Simanjutak, Meitisa Vanya (Universitas Nusa Cendana, 2025)
This study aims to analyze and find out the obstacles in the collaboration between the Peace Circle Foundation and BNPT in the success of the Deradicalization Program for terrorism inmates in the Class I Correctional Institution of Surabaya. Collaboration is important in the implementation of the deradicalization program; it is in accordance with Government Regulation Number 77 of 2019 in Article 29 paragraphs (2), (3), and (4). The method used in this study is a qualitative method, with data collection techniques such as observation, interviews, and document studies. This research uses the theory of collaborative governance. The results of this study show that the collaboration carried out in the implementation of the deradicalization program at the Class I Correctional Institution in Surabaya proves that there is good communication between parties, and all parties feel that they have and share mutual understanding of all problems and successes, and all terrorism inmates who have pledged to the Republic of Indonesia also show changes in their personalities by wanting to pray in congregation in mosques, participating in elections, participating in independence coaching, participating in competitions held by prisons, and participating in deradicalization programs from BNPT. However, in the implementation of this collaboration, there are obstacles such as the absence of an official cooperation agreement between the Surabaya Class I Prison and the Peace Circle Foundation, the lack of face-to-face meetings that are only held 4 times a year for officer changes, and the absence of a special DIPA for deradicalization. Keywords: Collaboration; Deradicalization Program; Terrorism Prisoners